Preparation of chitosan–hexaconazole nanoparticles as fungicide nanodelivery system for combating Ganoderma disease in oil palm - Maluin, Farhatun Najat; Hussein, Mohd Zobir; Yusof, Nor Azah; Fakurazi, Sharida; Abu Seman, Idris; Zainol Hilmi, Nur Hailini; Jeffery Daim, Leona Daniela (MDPI, 2019)
Fungicide is used to control fungal disease by destroying and inhibiting the fungus or fungal spores that cause the disease. However, failure to deliver fungicide to the disease region leads to ineffectiveness in the disease control. Hence, in the present study, nanotechnology has enabled the fungicide active agents (hexaconazole) to be encapsulated into chitosan nanoparticles with the aim of developing a fungicide nanodelivery system that can transport them more effectively to the target cells (Ganoderma fungus). A pathogenic fungus, Ganoderma boninense (G. boninense), is destructive to oil palm whereby it can cause significant loss to oil palm plantations located in the Southeast Asian countries, especially Malaysia and Indonesia. In regard to this matter, a series of chitosan nanoparticles loaded with the fungicide, hexaconazole, was prepared using various concentrations of crosslinking agent sodium tripolyphosphate (TPP). The resulting particle size revealed that the increase of the TPP concentration produced smaller particles. In addition, the in vitro fungicide released at pH 5.5 demonstrated that the fungicide from the nanoparticles was released in a sustainable manner with a prolonged release time up to 86 h. On another note, the in vitro antifungal studies established that smaller particle size leads to lower half maximum effective concentration (EC50) value, which indicates higher antifungal activity against G. boninense.